Weather risk in the functioning of water-sewage companies in Poland - Rak, Janusz; Wartalska, Katarzyna; Kaźmierczak, Bartosz (Instal, 2021)
Water and sewage companies are entities particularly sensitive to fluctuations in weather factors. This problem is particularly important in the face of progressive climate change. The article presents the current state of knowledge on the analysis and assessment of weather risk. Three new weather indexes for water supply and sewage systems in Poland were proposed so that these enterprises could effectively start managing the weather risk: daily precipitation index, frost day index, and hot day index. Their frequency was also verified based on data from 19 meteorological stations from the period 1970–2019. It has been shown that the analyzed weather indices were exceeded in the past once every 6 years, on average. Particular attention should be paid to very hot days and nights, which occur relatively rarely, but there is a clear trend in their frequency. The analysis also showed that global warming does not affect the frequency of reaching the frost day index.